(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
A further computing paradigm is cloud computing in data innovation. Cloud computing is characterized by the National Institute of Standards and Technology (NIST) as taking into account the ubiquitous, helpful, on-demand organize access to a mutual pool of configurable computer assets. In this study we focused on data storage system model in cloud computing paradigm and data security issues are listed on cloud system as well as challenges.